Prevalence of Intestinal Endoparasites With Zoonotic Potential in Domestic Cats From Botucatu, SP, Brazil - de Souza, Fúlvia Bueno [UNESP]; Nakiri, Isabela Maciel [UNESP]; Lourenço, Natália de Oliveira [UNESP]; da Silva, Gustavo Gomes [UNESP]; Paschoalini, Débora Rizzo [UNESP]; Guimarães-Okamoto, Priscylla Tatiana Chalfun [UNESP]; Melchert, Alessandra [UNESP] (Elsevier, 2017)
Intestinal endoparasites in cats have received increasing attention worldwide due to the increase in the population of cats and their intimate relationship with people. However, concern about the zoonotic potential of these agents is still small. The aim of this study was evaluating the occurrence of intestinal endoparasites, the most prevalent ones, as well as the profile of affected cats. We conducted a survey of the medical records of cats treated at Small Animal Medical Clinic, in the Veterinary Hospital of the University of Veterinary Medicine and Animal Sciences—campus Botucatu, São Paulo, Brazil. Medical records between January 2011 and September 2015 were evaluated, including all cats presenting with gastrointestinal clinical disorders and had positive parasitological stool sample tests (Faust and Willis techniques) for any type of endoparasite. We evaluated the data obtained from these cats, such as sex, breed, age, diet, street access, history of parasitic diseases and season of the year. From the 1725 cats evaluated during this period, there were a total of 60 positive cases. Among these cats, 60% were males and 40% were females. Regarding breeds, 68.3% were mixed breeds, 21.7% Persian, 8.3% Siamese, and 1.7% Himalayan. The ages ranged from 1-11 years old, with an average age of 2 years and 5 months. However, cats up to 6-months old were the most frequently affected. The highest incidence of parasitized cat was for Giardia sp. (65.0%), followed by Ancylostoma spp. (40.0%), Dipylidium caninum and Toxocara cati (8.3% each). It was observed that 65% of cats presented single infections and 35% mixed infections. This survey analyzed only positive cases of gastrointestinal endoparasites, so it diverges in some respects from other results in the literature. Asymptomatic cats were not considered, but they may be carriers that eliminate parasites in the environment. However, all intestinal endoparasites isolated in cats in this study represent a potential risk of zoonotic infections, which highlights the importance of this data for the adoption of preventive measures, especially in young male cats, which were the most frequently affected in this study and in others.
Keywords: Brazil; copro-parasitological examination; feline; parasitosis